The Use of the Armenian Stress. Linguistic Traditions of Armenia as a Context of Punctuation - Karapetyan, Mariam (Bulletin of Yerevan University B: Philology, 2024)
The article discusses the use of stress in the written Armenian, in particular, with regard to punctuation of imperative verb forms, as well as vocatives. Practical examples of the use of vocatives and imperative verbs raise the question of whether to stress or not. The article argues that avoiding stress in many cases is not a sign of laziness or ignorance of a grammatical rule, and that the need to understand current usage examples and trends leads particulary in the direction of one of the fields of linguistics - pragmatics. One of the questions underlying the article is whether the conceptualization of pragmatics, created by Charles Morris in 1930 and developed as a branch of linguistics in the 1970s, can reduce the “historical distance”, that is, lead to a rethinking of the accumulated traditions of linguistics in Armenia. Accordingly, one of the main goals of the article is to raise the question of the pragmatic potential of punctuation marks. In pursuit of this goal, the question is raised, isn't it time to change the rules of stress?The rules of obligatory stress are also considered in relation to other linguistic levels, such as morphology, syntax, semantics, as well as from the point of view of one of the linguistic areas - sociolinguistics. A number of statements by Armenian and foreign linguists are discussed, creating a range of approaches with which the rules for the use of punctuation marks and, in particular, stress can be correlated.
Keywords: the opposition of language and speech; the use of stress; punctuation of the imperative mood; punctuation of vocatives; the relationship of linguistic levels; the social significance of the linguistic form; the pragmatic potential of stress